Morphological Characteristics and Antagonist Test Trichoderma sp. Against Fungi Helminthosporium sp. Causing Leaf Blight Disease in Corn Plants In Vitro - Santoso, Ardelia Qonita; Siahaan, Parluhutan; Baideng, Eva (JURNAL BIOS LOGOS, 2025)
Helminthosporium sp. is an organism that causes leaf blight disease in corn plants, thus becoming one of the causes of declining production in the agricultural sector. Lack of awareness and low knowledge of farmers in control efforts that still use synthetic pesticides that have a negative impact on the environment and health, therefore the use of antagonistic microbes that live around plant roots such as Trichoderma sp. is one way to control environmentally friendly soil-borne pathogens. This study aims to analyze the characteristics of Trichoderma sp. and Helminthosporium sp. macroscopically and microscopically and to test the antagonistic ability of Trichoderma sp. fungi based on competition tests, antibiosis tests and mycoparasitism tests against Helminthosporium sp. fungi isolate Tondegesan. Trichoderma sp. fungal antagonist test against Helminthosporium sp. fungi using the duo plate assay method in Potato Dextrose Agar (PDA) media in vitro. The results showed that Trichoderma sp. fungi. has macroscopic morphological characteristics of dark green colonies with fine cotton fibers and microscopic morphological characteristics of green septate hyphae, upright conidiophores and many branches. Helmintosporium sp. fungi have macroscopic morphological characteristics of flat fibrous colony surfaces, oval shapes with slightly brownish white colors and microscopic morphological characteristics of fairly thick hyphal walls with yellowish brown colors. Based on the antagonist test, Trichoderma sp. fungi have an inhibition percentage of 71% against Helminthosporium sp. fungi on the seventh day.